Grundtvig og den lutherske tradition - Jørgensen, Theodor Holzdeppe (Grundtvig-studier, 1998)
Grundtvig and the Lutheran Tradition By Theodor Jørgensen The essay analyses the relation of Grundtvig to the Lutheran tradition in the form it took in Orthodoxy and early Protestantism, primarily on the basis of Grundtvig’s essay from 1830: » Should the Lutheran Reformation Really Be Continued?«. Grundtvig gives an affirmative answer to this question. In elaboration the present writer points out that in his dispute with Lutheran orthodoxy as well as modem Protestantism Gmndtvig upholds the main concern of the Reformation, but in the context of Modernity.This finds its most significant expression in Gmndtvig’s rejection of the ’sola scriptura’ of the Reformation, the Scriptures as the foundation of Christian Faith. The foundation of Faith is the living Christ, present in the word of Faith, Baptism and Eucharist amidst the congregation celebrating the divine service. On the other hand the Holy Scripture retains its authority as the best book of enlightenment for Faith. Grundtvig is convinced that with this view of the Scriptures he legitimizes the freedom for Bible research and theology which they rightly demand.